2015
DOI: 10.21275/v4i12.29111506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen and Phosphorus Fertilizers on Growth and Yield of Quality Protein Maize (QPM)

Abstract: Abstract:Response of quality protein maize hybrid (HQPM-1) to various N and P levels was studied at College Farm, College of Agriculture, Rajendranagar, Hyderabad during kharif 2012. Quality protein maize was tested with four nitrogen levels (0, 120, 180 and 240 kg N ha -1 ) and four phosphorus levels (0, 60, 80 and 100 kg P 2 O 5 ha -1 ) which was laid out in randomized block design with three replications at a spacing of 60 × 20 cm. Results showed that each incremental effect of nitrogen and phosphorus ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…At all the levels of N, application of FYM 15 significantly increased the stover yield over FYM 0 but further increase to FYM 22.5 failed to increase significantly. Jena et al (2013) [42] concluded that increase in the level of N significantly increased the stover yield. Amanullah et al (2015) [43] reported that application of 120 kg N ha -1 significantly increased the stover yield.…”
Section: Resultsmentioning
confidence: 99%
“…At all the levels of N, application of FYM 15 significantly increased the stover yield over FYM 0 but further increase to FYM 22.5 failed to increase significantly. Jena et al (2013) [42] concluded that increase in the level of N significantly increased the stover yield. Amanullah et al (2015) [43] reported that application of 120 kg N ha -1 significantly increased the stover yield.…”
Section: Resultsmentioning
confidence: 99%
“…However, the treatment -8(Nitrogen 100 kg/ha + Phosphorus 40 kg/ha) was found to be statistically at par with treatment-9 (Nitrogen 100 kg/ha + Phosphorus 50 kg/ha) in (Table 2). "Significant and maximum crude protein was recorded with application of nitrogen (100kg/ha) might be due to nitrogen is an active ingredient of protein molecule and a building block of amino acid results in linear increase in crude protein with increased nitrogen levels" Sewhag et al [15,[16][17][18][19][20].…”
Section: Crude Protein Content (%)mentioning
confidence: 99%
“…day -1 ) were gained by the application of 520 kg urea ha -1 . Jena et al (2015) proposed that the larger height of the plant (212.75 cm) and a higher leaf area index (3.89) were obtained from the application of 240 kg nitrogen ha -1 as compared to control treatments. Rihab et al, 2015 conducted a field experiment and explained about the effect of different levels of nitrogen in maize field under plant density (Table 1).…”
Section: Growth and Growth Componentsmentioning
confidence: 99%
“…The same result was proposed by Khan et al (2014) who concluded that highest yield was received by the application of nitrogen substance properly with the proper dose. Jena et al (2015) from Andhra Pradesh, conducted an experiment on maize crop and proposed that the highest amount of dry matter produced (13432 kg ha -1 ) by the petition of 240 kg nitrogen ha -1 respectively, while the lowest dry matter production (4022 kg ha -1 ) was observed in the control condition. Kar et al (2016) reported that higher dry matter (21.66%) and higher yield of dry matter (83.77 q ha -1 ) were executed by the application of the proper recommended dose of fertilizer.…”
Section: Yields and Yield Attributesmentioning
confidence: 99%
See 1 more Smart Citation